Forecasting Air Quality Indicators for 33 Cities in China. Issue 1 (12th December 2019) - Wu, Lifeng; Zhao, Hongying
Abstract: The Jing‐Jin‐Ji (Beijing‐Tianjin‐Hebei) and the surrounding Jin‐Lu‐Yu (Shanxi‐Shandong‐Henan) regions are experiencing severe problems with air pollution. To measure the change in pollutant concentrations over the next few years, the fractional order accumulation grey model is used to forecast the air quality indicators. The results show that the concentrations of fine particulate matter, particulate matter 10, and sulfur dioxide show a downward trend, and 8‐h O3 (annual) and 8‐h O3 (spring and summer) show an upward trend in these areas. There is a slight increase in nitrogen dioxide concentration in Shanxi, but its concentration in other areas shows a slight decline. The results obtained can provide a clear direction for air quality management decisions. Abstract : The Jing‐Jin‐Ji (Beijing‐Tianjin‐Hebei) and the surrounding Jin‐Lu‐Yu (Shanxi‐Shandong‐Henan) regions are experiencing severe problems with air pollution. The study aims to comprehensively assess the pollution status of 33 cities around Jing‐Jin‐Ji. The atmospheric pollution transmission channel is predicted by using the grey model with fractional order accumulation. The results will provide a clear direction for air quality management decisions.